5PSQ-038 Drug related visits to the emergency department in nursing home patients. Issue 1 (23rd March 2023) - Ana, J; Pedemonte, M; Socias, C; Santos, M; Puig, M; Mangues, MA; Ruiz, J
Abstract : Background and Importance: Drug related problems (DRPs) are one of the main causes requiring assistance to the Emergency Department (ED) in frailty people. Many of these patients live in nursing homes (NH). Identifying the differential characteristics of patients and DRPs that cause consultation in this subgroup, can help to improve the pharmaceutical care programs implemented in our environment in NH. Aim and Objectives: To identify drugs that are associated with DRPs that causes consultation of ED in patients coming from NH and compare the drugs involved, and the characteristics and comorbidities of these patients with non-NH patients. Material and Methods: Retrospective, descriptive observational study was conducted between February 21-May 2022 in the ED of a university hospital. We included adult patients who attended ED for DRPs. The following variables were collected and compared between NH patients and no NH patients: age, sex, chronic pathologies at admission, number of drugs prescribed in the electronic prescription, drug involved in the DRPs and diagnosis related to the DRPs. Qualitative variables have been compared between the NH patients vs no NH patients using the Chi-Square test and quantitative variables using the independent data t-test. Results: 1029 patients were included. 98 of them (9.53%) were referred from NH nh patients were older (84, 6 (8.9) years old vs 77, 1 (15.7) P<0.001*), mostly women [64 (65.3%) vs 511 (54.8%) P=0, 046*], with a higher percentage of cognitive impairment [59 (60.2%) vs 189 (20.0%) P<0.001*], severe functional dependence [68 (69.3) vs 216 (23.2) P<0.001*] and severe polypharmacy (>=10 home medications) [53 (54.0%) vs 276 (29.6%) P<0.001] than the rest of the patients who consulted the ED for DRPs. DRPs related to the ATC group C (cardiovascular system) were more prevalent in NH patients [21 (21.4% ) vs 310 (33.2%) P=0.017*] as well as diagnostics gastrointestinal motility disorders [23 (23.4%) vs 129 (13.8%) P=0.011*] and confusional syndromes [5 (5.1% ) vs 17 (1.8) P=0.031*] Conclusion and Relevance: NH patients that consult ED for DRPs were older, mostly women with a high degree of socio-functional, cognitive dependence and extreme polypharmacy than no NH patients. DRP related with C ATC group and diagnosis of confusional syndrome and gastrointestinal motility disorders are also more prevalent. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.